Cortical–striatal gene expression in neonatal hippocampal lesion (NVHL)‐amplified cocaine sensitization. (22nd June 2013) - Chambers, R. A.; McClintick, J. N.; Sentir, A. M.; Berg, S. A.; Runyan, M.; Choi, K. H.; Edenberg, H. J.
Abstract : Cortical–striatal circuit dysfunction in mental illness may enhance addiction vulnerability. Neonatal ventral hippocampal lesions (NVHL) model this dual diagnosis causality by producing a schizophrenia syndrome with enhanced responsiveness to addictive drugs. Rat genome‐wide microarrays containing >24 000 probesets were used to examine separate and co‐occurring effects of NVHLs and cocaine sensitization (15 mg/kg/day × 5 days) on gene expression within medial prefrontal cortex (MPFC), nucleus accumbens (NAC), and caudate‐putamen (CAPU). Two weeks after NVHLs robustly amplified cocaine behavioral sensitization, brains were harvested for genes of interest defined as those altered at P  < 0.001 by NVHL or cocaine effects or interactions. Among 135 genes so impacted, NVHLs altered twofold more than cocaine, with half of all changes in the NAC. Although no genes were changed in the same direction by both NVHL and cocaine history, the anatomy and directionality of significant changes suggested synergy on the neural circuit level generative of compounded behavioral phenotypes: NVHL predominantly downregulated expression in MPFC and NAC while NVHL and cocaine history mostly upregulated CAPU expression. From 75 named genes altered by NVHL or cocaine, 27 had expression levels that correlated significantly with degree of behavioral sensitization, including 11 downregulated by NVHL in MPFC/NAC, and 10 upregulated by NVHL or cocaine in CAPU. These findings suggest that structural and functional impoverishment of prefrontal‐cortical‐accumbens circuits in mental illness is associated with abnormal striatal plasticity compounding with that in addictive disease. Polygenetic interactions impacting neuronal signaling and morphology within these networks likely contribute to addiction vulnerability in mental illness . Abstract : Cortical‐striatal gene expression in a schizophrenia model point to ingredients for addiction vulnerability in mental illness.